Dicţionarul general al literaturii române – enciclopedie a literaturii și culturii naționale - Laurențiu Hanganu (Revista de Istorie și Teorie Literară)
The most comprehensive, representative and imposing lexicographic work of the Romanian literary history and criticism, the General Dictionary of Romanian Literature is a real encyclopedia of our national literature and culture. An encyclopedia made by augmenting the interpretative and informational data (articles on authors, editors, translators, literary publications, institutions etc.) with synthetic studies on literary and cultural movements that contributed in an essential way to the process of defining and structuring the Romanian literature as literature. Having as its pillars the great personalities of M. Eminescu, I.L. Caragiale, Ion Creangă, Tudor Arghezi, Mihail Sadoveanu, Camil Petrescu, Nichita Stănescu, Marin Preda – but also those of Eugen Ionescu, Emil Cioran and Mircea Eliade – the General Dictionary of Romanian Literature represents an invaluable thesaurus of Romanian culture and spirituality.